Implementation of the "Acep Belajar" Program for Improving the Quality of Learning at SMPN 2 Tanasitolo, Tanasitolo District - Muhammad Arifai; Nurjannah Nurjannah; Fakhruddin Fakhruddin; Najmiah Najmiah; Gunawan Gunawan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
The report on the results of research on the activities and student achievement at SMP Negeri 2 Tanasitolo through the application of learning. "Research was conducted by students to help students who still experience learning problems, especially the lack of student interest in education. This study aims to determine the effect of implementing the Acep Belajar program on learning activities, creativity, student learning achievement and the effectiveness of classroom management. This research was carried out in class VIII B of SMPN 2 Tanasitolo from January to May 2019 which was divided into two cycles including the preparation (planning), implementation of the action, observation, evaluation, reflection, and revision of stories. Data analysis was carried out descriptively and presented in tabular form and the calculation of the percentage of results. The results of the research obtained from the first cycle, the average value of student learning outcomes was 60.70, while in the second cycle, it was 83.70. Students who get the highest score in the process I am 20% in cycle II to 40%. Thus there is an increase in student achievement compared to conventional cooperative methods which are only able to achieve the highest score, which is still below 20% or around 4%. Besides that, student learning activities in the discussion were below 12% after the second cycle increased to 16%. Furthermore, it was concluded that the implementation of the Acep learning program could significantly improve the quality of learning for class VIII B students of SMPN 2 Tanasitolo.